Landscape, ritual and identity among the Hyolmo of Nepal - Torri, Davide (Routledge, 2020)
"This book analyses the social, political and religious life of the Hyolmo people of Nepal. Highlighting patterns of change and adaptation, it addresses the Shamanic-Buddhist interface that exists in the animated landscape of the Himalayas. Opening with an analysis of the ethnic revival of Nepal, the book first considers the Himalayan religious landscape and its people. Specific attention is then given to Helambu, home of the Hyolmo people, within the framework of Tibetan Buddhism. The discussion then turns to the persisting shamanic tradition of the region and the ritual dynamics of Hyolmo culture. The book concludes by considering broader questions of Hyolmo identity in the Nepalese context, as well as reflecting on the interconnection of landscape, ritual and identity. Offering a unique insight into a fascinating Himalayan culture and its formation, this book will be of great interest to scholars of indigenous peoples and religion across religious studies, Buddhist studies, cultural anthropology and South Asian studies"--
Includes bibliographical references and index
Keywords: Helmu (Nepal) -- Religion; Schamanismus; Tibetischer Buddhismus; Nepal; Schamane; Lama; Helambu Sherpa